Empires and encounters 1350-1750 - Reinhard, Wolfgang (A history of the world, 2015)
Empires and Encounters presents information on different aspects of human life in all parts of the world from the period 1350 to 1750. The chapters of the book examine Eurasia between Japan and Russia; the Ottoman and Iranian Empires of the Muslim world; Mughal India and the trading world of the Indian Ocean; the multicolored world of maritime Southeast Asia and Oceania; and the continents on both sides of the Atlantic under the growing impact of Europe. Europe at this time had no privileged power position, but it did enjoy a special role in establishing regular maritime interaction across the Atlantic and worldwide between the five macro-regions of the globe. The European world economy, based upon the silver of Spanish America, initiated modern globalization.